The Peranan Manajemen Pengelolaan Keuangan Islam Untuk Menghindari Gaya Hidup Shopaholic Sebagai Bentuk Perilaku Konsumtif ( Pada Santriwati Prodi Ekonomi Syari’ah Ponpes Putri Darullughah Wadda’wah) - Fitriyah, Wardatul (Airlangga Journal of Innovation Management, 2024)
The increasing number of human needs for life, the increasingly demanding patterns of lifestyle improvements, and the culture of consumerism make some people not aware that they have spent their money without calculating it, low desire to save and knowledge of investing in the future is still less than optimal in management. This research is descriptive research with a qualitative approach. The researcher will describe and describe the social and economic life of Islamic boarding school students in Dalwa who already have personal financial goals (pocket) to plan, direct, and control financial activities, both expenses and income, to get used to a simple lifestyle, not consumptive, manage and plan shopping & consumption decision while at the cottage. From the results of field data analysis, it is clear that the application of 5 concepts of Islamic management behavior patterns is: spending/ controlling money according to needs rather than desires, paying obligations on time, planning finances for future needs/making a list of priorities, saving/setting aside pocket money and rational consumption (mustahliq al-aqlani) spending income according to needs. Every student is expected to have the ability to direct & control the use of pocket money as a solution to irrational consumption that tends to be thrifty and avoids the shopaholic lifestyle